1980
DOI: 10.1084/jem.152.2.280
|View full text |Cite
|
Sign up to set email alerts
|

T cell subsets defined by expression of Lyt-1,2,3 and Thy-1 antigens. Two-parameter immunofluorescence and cytotoxicity analysis with monoclonal antibodies modifies current views.

Abstract: Antibodies to mouse T cell antigens such as Thy-1, Lyt-1, Lyt-2, and Lyt-3 have been used to characterize T cell subpopulations and to determine precursor-progeny relationships (1). Although the original Lyt-l+2 ÷, Lyt-l+2 -, and Lyt-l-2 ÷ classifications have been very useful, several recent findings appear to be inconsistent with the model proposed by Cantor and Boyse, i.e., that Lyt-l+2 ÷ immature T cells give rise to Lyt-1+2-helper cells and Lyt-1-2 + cytotoxic and suppressor cells (1) For example, cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(119 citation statements)
references
References 22 publications
4
115
0
Order By: Relevance
“…Both human and mouse splenic T populations contain two antigenically and functionally distinct subsets: helper-inducer and suppressor-cytotoxic, which are specifically recognized by a series of monoclonal antibodies (3)(4)(5)(6). In terms of percentages of cells stained and staining profiles, none of the anti-rabbit monoclonals closely resembled the subset-specific anti-mouse or anti-human reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Both human and mouse splenic T populations contain two antigenically and functionally distinct subsets: helper-inducer and suppressor-cytotoxic, which are specifically recognized by a series of monoclonal antibodies (3)(4)(5)(6). In terms of percentages of cells stained and staining profiles, none of the anti-rabbit monoclonals closely resembled the subset-specific anti-mouse or anti-human reagents.…”
Section: Discussionmentioning
confidence: 99%
“…By the combination of flow cytometry, a microculture system for the activation of unprimed lymphocytes at limiting dilution, and sensitive microassays for cytolytic and lymphokine activities, it has been possible to compare directly in each series of microcultures the frequencies of lymphokine-secreting cells and cytolytic T lymphocytes in populations separated according to Lyt-2 phenotype. The Lyt-1 phenotype was not taken into consideration in this study in view of recent demonstrations by several laboratories that this marker is expressed by essentially all T lymphocytes (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Both Pang et al (27) and Ashman and MuUbacher (28) have demonstrated that for Lyt 2+ cytotoxic T cells to be generated in vitro, Lyt 1 ^ cells are required to be present. In this work we used the L3T4 surface antigen as a marker for helper T cells rather than the Lyt 1 antigen because expression of L3T4 and Lyt 2 by spleen cells appears to be mutually exclusive (29) and the expression of L3T4 differs from that of Lyt 1 in that Lyt 1 is expressed by all splenic T cells, albeit at a lower density on Lyt 2 cells (30).…”
Section: Phenotype Of Responder Cells Necessary For the Generation Ofmentioning
confidence: 99%